Crocetin Attenuates Sepsis-Induced Cardiac Dysfunction via Regulation of Inflammatory Response and Mitochondrial Function - Wang, Yanpeng; Yu, Weiwei; Shi, Chenhui; Hu, Pengfei (Frontiers in Physiology, 2020)
Sepsis-induced systemic inflammatory response dominants an important role in cardiac dysfunction, which is a mortal injury to cause heart failure. It is emerging that find a natural drug/compound to prevent sepsis-induced cardiac dysfunction. Crocetin (CRO) is a natural compound to reduce inflammation and cytotoxicity in cardiac ischemia/reperfusion injury. Whether CRO has the ability to alleviate sepsis-induced cardiac dysfunction remains unknown. Here we applied an in vitro model of sepsis by using LPS-induced H9c2 cells. CRO significantly alleviated LPS-induced cytotoxicity, cellular apoptosis and oxidative stress by increasing Bcl-2 activity, PI3K-Akt signaling and suppressing caspase 3 and caspase 9 activities. In aspect of LPS-induced inflammatory response, CRO dramatically decreased mRNA levels of TNF-α, IL-1, IL-6 and IL-8 via suppressing p65/Keap1 signaling and activating Nrf2/HO-1/NQO1 signaling. We further demonstrated CRO maintained mitochondrial respiration function, free fatty acid β-oxidation and mitochondrial morphology, in LPS-induced cardiac sepsis. Taken together, CRO attenuates sepsis-induced cardiac dysfunction via regulation of inflammatory response and mitochondrial functions.